THE IMPACT OF COVID-19 ERA ON THE STUDENTS’ ENGLISH COMMUNICATION - Syarifuddin Syarifuddin; Gunawan Gunawan (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This research was aimed at finding out the impact of the COVID-19 era on English students' communication skills at the University of Muhammadiyah Bone. This research was a descriptive qualitative design. The source data was from the students of the English education department. This research used a purposive sampling technique. The students were 20 and were taken from the English education department. The instruments of this research were interviews and questionnaires. The data from the students' interviews were transcribed and analyzed to answer the research question about the impact of the COVID-19 era on the English students' communication skills at the University of Muhammadiyah Bone. The results from the questionnaire showed that students mostly had a negative response to learning to speak during the COVID-19 period. The interview showed that the students' answers also gave negative responses toward the impact of the COVID-19 era on their English communication skills. It means that they want to learn to speak offline. They want to learn to speak with maximum support so that they do not feel bored easily or nervous about communicating. According to the data from both instruments, most students were not having fun, feeling confident, enjoying themselves, or being motivated to learn through online speaking. Furthermore, most want to learn to speak in a physical classroom rather than a virtual one.